Pengaruh Audit Lag, Ukuran Perusahaan, dan Prior Opinion terhadap Opini Audit Going Concern - Yunita Susilawati; Hengky Leon (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
The going concern audit opinion is one of the key indicators in assessing a company’s business continuity, particularly in the transportation and logistics sector which plays a strategic role in supporting economic activities. This study aims to analyze the effect of audit lag, company size, and prior opinion on the issuance of going concern audit opinions in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The research employed a quantitative approach using secondary data consisting of annual financial statements and independent audit reports. The research sample was determined using purposive sampling, resulting in 84 observations from 28 transportation and logistics companies. Data analysis was conducted using logistic regression with the aid of SPSS version 26. The results revealed that audit lag, company size, and prior opinion did not have a significant partial effect on going concern audit opinions. These findings indicate that the mentioned factors are not the main determinants for auditors in issuing audit opinions related to business continuity. This study contributes to the accounting and auditing literature and provides insights for auditors, investors, and company management in understanding relevant factors influencing going concern audit opinions.